Taqwa Sebagai Paradigma Transformasi Kehidupan: Analisis Tematik Terhadap Ayat-Ayat Taqwa Dalam Al-Qur'an - Haswani Ansar; Hasyim Haddade; Hamka Ilyas (CV. SINAR HOWUHOWU, 2026)
This study aims to analyze the concept of taqwa in the Qur'an as a paradigm for life transformation that is relevant to addressing ethical challenges in the digital society. The research employed a descriptive qualitative approach using library research and thematic interpretation (tafsīr maudhū'ī) of 259 Qur'anic verses related to taqwa. Data were collected from the Qur'an, classical and contemporary tafsir literature, as well as relevant academic sources. Data analysis followed the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings reveal that taqwa is a multidimensional concept consisting of four main dimensions: theological, spiritual, moral, and social. Based on these findings, the study proposes a conceptual model of taqwa comprising five components: divine consciousness, active obedience, self-control, social justice, and moral transformation. This study contributes to the development of thematic Qur'anic interpretation by integrating Sufism and sociology of religion perspectives. Furthermore, the findings demonstrate that the values of taqwa can serve as a foundation for character education and digital ethics in responding to contemporary moral challenges.